Usage of double injector for efficient mixing of the fuel behind the ramp injector at supersonic combustion chamber - Ihab Omar; Mohamed R. El-Sharkawy; Rifaqat Ali; Pradeep Kumar Singh; Husam Rajab; Mohsen Ahmed; Naim Ben Ali; Wajdi Rajhi; Lotfi Ben Said; S. Arman Abodollahi (Scientific Reports)
Abstract This investigation presents extensive computational analyses of the compressible flow near ramp injector with double circular injectors at supersonic combustor of scramjet engine. Comparison of the fuel mixing and fuel jet penetration of hydrogen jet are done for two injector configurations at free stream Mach number of 2. The simulation of the supersonic flow near ramp injector is done via solving RANS equations with computational fluid dynamic technique. Effect of nozzle space on the fuel distribution and mixing mechanism has been investigated. Besides, interface of the free stream and jet behind the ramp are fully analyzed. Comparison of the circulation strength behind these two configurations indicates that increasing of the jet space led to higher circulation strength. However, the mixing efficiency of the model with low jet space is higher since the interaction of these two jet is key factor for diffusion and mixing inside the combustion chamber.